Penerapan Keselamatan dan Kesehatan Kerja: Studi kasus Pada PT Mega Cipta Bangsa - Cantika, Dinda Ayuni; Sofyan, Mohammad (CV ODIS, 2024)
Occupational safety and health (K3) is an essential aspect of the manufacturing industry, significantly reducing the risk of workplace injury and disease. This research aims to evaluate the implementation of K3 at PT Mega Cipta Bangsa, a leading manufacturing company that produces Miniature Circuit Breakers (MCB). The research method uses a descriptive approach by analyzing literature reviews and conducting interviews with company HSE staff and managers. The results show that PT Mega Cipta Bangsa has implemented various K3 policies and programs, including the Occupational Safety and Health Management System (SMK3), by national and international standards. Apart from that, the company also has a strong safety culture and carries out internal SMK3 audits on a scheduled basis. Implementing K3 at PT Mega Cipta Bangsa improves employee safety and health and increases their satisfaction, morale, and performance. Apart from that, implementing K3 also helps companies reduce costs and losses and comply with applicable regulations. In conclusion, the effective implementation of K3 at PT Mega Cipta Bangsa positively impacts employees and company operations.